INVESTIGATING THE ACTIVE CHEMICALS IN BAY LEAVES IN SUPPRESSING MICROBES AND IMPROVING THE SENSORY PROPERTIES OF CHILLED CHICKEN MEAT - M. A. Qasim; A. A. Al-Azzami; N. T. Khaleel; A. A. Yaseen; M. M. Fahad (مجلة الأنبار للعلوم الزراعية)
This study aimed to qualitatively identify the active components in bay leaf extracts and their inhibitory function. While saponins and glycosides were absent, the research did find flavonoids, tannins, alkaloids, phenols, steroids, and terpenes. The investigation showed that the alcoholic extract (ethanol 99.8%) outperformed the aqueous extract in preventing the development and activities of four different types of gram-positive and gram-negative bacteria. The space created by the alcoholic extract was surrounded by a clear zone measuring 18.8, 15.5, 19.48, and 16.8 mm in diameter for the Escherichia coli, Salmonella typhi, Staphylococcus aureus, and Bacillus cereus culture media, respectively compared to the 10.5, 8.5, 9.4, and 9.1 mm for the aqueous extract. In that order, 1.5% of the alcoholic extract was added at a rate of 0.5, 0.57, and 1.0%. The study's findings also showed that, after 12 days of refrigeration, adding varying amounts of alcoholic extract to chicken meat greatly enhanced its microbiological quality. In the treatment containing 1.5% of the alcoholic extract, the total count of microorganisms, psychrophilic and coliform, reached 7.470, 4.950, and 3.823 cfu\gram, while in the control it was 9.695, 5.873, and 5.386 cfu\gram, respectively. Also, after 12 days of refrigerated storage, the addition of the alcoholic extract enhanced all sensory aspects of the chicken meat as well as its overall level of acceptability.